The Potential Emergence of “Education as Mental Health Therapy” as a Feasible Form of Teacher-Delivered Child Mental Health Care in a Low and Middle Income Country: A Mixed Methods Pragmatic Pilot Study - Cruz, Christina M.; Giri, Priscilla; Vanderburg, Juliana L.; Ferrarone, Peter; Bhattarai, Surekha; Giardina, Aileen A.; Gaynes, Bradley N.; Hampanda, Karen; Lamb, Molly M.; Matergia, Michael (Frontiers in Psychiatry, 2021)
Objective: We assessed task-shifting children's mental health care to teachers as a potential approach to improving access to child mental health care. Methods: In Darjeeling, India, we conducted a single-arm, mixed-methods feasibility study with 19 teachers and 36 children in five rural primary schools to determine whether teachers can deliver transdiagnostic mental health care to select children-in-need with fidelity to protocol, to assess which therapeutic options teachers chose to use within the protocol, and to evaluate for a potential signal of efficacy. Results: Participation rates for intervention activities were >80%. A majority of teachers met or exceeded quality benchmarks for all intervention activities. Teachers chose to deliver teacher-centric techniques, i.e., techniques that only teachers could deliver given their role in the child's life, 80% of the time. Children improved in mental health score percentiles on the Achenbach Teacher Report Form. Key facilitators included the flexibility to adapt intervention activities to their needs, while identified barriers included limited time for care delivery. Conclusion: Findings support the feasibility of task-shifting children's mental health care to classroom teachers in resource-limited schools. Fidelity to protocol appeared feasible, though the freedom to choose and adapt therapeutic techniques may also have enhanced feasibility. Surprisingly, teachers consistently chose to deliver teacher-centric therapeutic techniques that resulted in a potential signal of efficacy. This finding supports the potential emergence of “education as mental health therapy” (Ed-MH) as a new therapy modality. Continued investigation is required to test and refine strategies for involving teachers in the delivery of transdiagnostic mental health care.